Engineering investigations of the recreating kinetics of flavour-components during the boiling of wort - Hertel, M.; Tippmann, J.; Sommer, K.; Glas, K. (BrewingScience, 2006)
An important effect of boiling wort is the recreation of aromatic compounds. Unwanted flavour-components are not only expelled, they are also recreated during the boiling of wort and the whirlpool rest. There are different opinions on which flavour-components are significantly recreated during the boiling of wort. Because of this, the aim of the research was to see which aromatic compounds go through a significant recreation at wort boiling temperatures and, thus, possibly during the whirlpool rest, too. On account of this the creation rates of unwanted flavour-components are measured in a closed reactor with a reflux condenser in order to inhibit calcination and thus get reliable results. After samples are taken at defined time intervals, they are immediately cooled down and analysed by gas chromatography (GC). This way the increase of flavourcomponents is measured and rate constants are acquired. To get a wide spectrum of different wort flavour-components the measurements were done for 2-Methylbutanal (2MB), 3-Methylbutanal (3MB), Phenylethanal, Benzaldehyde, 2-Furfural, γ-Nonalactone, Hexanal, 2-Phenylethanol and Dimethylsulfide (DMS) respectively S-Methylmethionine. These are important flavour-components that have to be reduced to below a defined level during the boiling of wort. If the calcination of these compounds, especially of DMS, is insufficient, off-flavour will occur in the resulting beer. This would also implicate worse flavour stability.The described method is able to determine the rate constants of the recreation of wort flavour-components. The results confirm the theory, that aroma compounds from fatty acids are not recreated during the boiling of wort and thus are not created in the whirlpool, either. For some compounds of the Strecker-degradation this is also applicable at current wort boiling times. For 2-Furfural and DMS the recreation must be implicitly considered.The new measurement results can be used to make a detailed prediction of the recreation of unwanted wort aroma compounds during the boiling of wort and the whirlpool rest.The main reason why these trials were done is that the results are needed for the calculation of exact residue curves of wort flavour-compounds during the boiling of wort. Residue curves can be calculated if the vapour-liquid-equilibrium of the flavour-components is known. In opposite to residue curves of flavour-components in pure water, where no recreation takes place, a possible recreation of compounds during wort boiling must be considered in the calculation of these curves in wort. Therefore rate constants are only measured at the atmospheric boiling temperature of wort for the purpose of this article.The results of this article are used for a planned follow-up article in this magazine, which discusses the steaming behaviour of the same flavour-components.